2018
DOI: 10.1177/0300060518788994
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum IS-10506 probiotic administration increases amlodipine absorption in a rabbit model

Abstract: Objective Probiotics are beneficial in human health. In this study, we investigated the effect of probiotics on absorption of amlodipine, a dihydropyridine calcium antagonist used in the treatment of angina and hypertension, in a rabbit model. Methods Lactobacillus plantarum IS-10506 probiotic was administered for 14 days to male New Zealand rabbits. Blood samples were collected before and after probiotic supplementation. Amlodipine (10 mg) was then administered to all groups. Blood samples from a marginal vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…Clear examples can be seen in rats fed with probiotics, who had a significant increase of amiodarone (antiarrhythmic agent) bioavailability [88]. A similar is noted in diabetic rats after they received gliclazide (antihyperglycemic agent) [89] and in rabbits after the administration of amlodipine (antiarrhythmic agent) [90]. Authors that studied amiodarone [88] proposed that the increase of its bioavailability by almost 43% is due to a decrease of pH in the intestine, which consequently, facilitated ionization of the amiodarone and impacted amiodarone transit.…”
Section: Drug Interactions Of Probioticsmentioning
confidence: 78%
See 2 more Smart Citations
“…Clear examples can be seen in rats fed with probiotics, who had a significant increase of amiodarone (antiarrhythmic agent) bioavailability [88]. A similar is noted in diabetic rats after they received gliclazide (antihyperglycemic agent) [89] and in rabbits after the administration of amlodipine (antiarrhythmic agent) [90]. Authors that studied amiodarone [88] proposed that the increase of its bioavailability by almost 43% is due to a decrease of pH in the intestine, which consequently, facilitated ionization of the amiodarone and impacted amiodarone transit.…”
Section: Drug Interactions Of Probioticsmentioning
confidence: 78%
“…As the probiotic survival differs for varies bacterial species, to define the specific strain, collecting feces can be used for studying probiotics in vivo. Other approaches include intestinal intubation or performing mucosal biopsies [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ,…”
Section: Safety and Pathogenicity Of Probiotics And Their Assessmementioning
confidence: 99%
See 1 more Smart Citation
“…There was a usual increase in the counts of Hb and RBCs in mice administered with L. plantarum MBTU-HK1 and acacia gum (i.e., in the probiotic group and the synbiotic group) compared with the control. [21] has reported that there was a significant increase in RBCs in an L. plantarum IS-10506-supplemented animal group, which plays a role in tissue oxygen delivery. Experiments in [22] concluded that the degradation of acacia gum brings about short chain fatty acids, which promote fetal hemoglobin expression in RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with amlodipine monotherapy, coadministration with Lactobacillus plantarum IS-10506 in rabbits significantly enhanced the amlodipine concentration. The authors speculated that L. plantarum IS-10506 could enhance red blood cells and hematocrit, leading to a lower sedimentation rate and increased levels of plasma proteins, which bind amlodipine (147). In addition, a live bacterial suspension of the probiotic Escherichia coli Nissle 1917 enhanced the bioavailability of amiodarone, which is an antiarrhythmic drug, in rats (148), and mixed cultures of Lactobacillus acidophilus, Bifidobacterium lactis, and Lactobacillus rhamnosus increased the bioavailability of gliclazide, an antidiabetic drug, in diabetic rats (149).…”
Section: Pathway 4: Inhibition Of Specific Gut Bacteria Transforming Parent Compounds Into Inactive Forms By Nonparent Compoundsmentioning
confidence: 99%